Unusual illudin-type sesquiterpenoids from cultures of Agrocybe salicacola - Liu, Liang-Yan (Springer Berlin Heidelberg, 2011)
Seven new illudin-type sesquiterpenoids, agrocybins A–G (1–7), along with three known analogues (8–10), have been isolated from the culture broth of the fungus Agrocybe salicacola. Their structures were elucidated on the basis of extensive spectroscopic data analysis and comparison with data reported in the literature. The relative stereoconfigurations of 1 and 6 were elucidated by the X-ray crystallographic diffraction analysis. Compound 1 was highly cyclized containing seven chiral carbons which arranged compactly in six rings. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-011-0018-4 and is accessible for authorized users.